Vocational School Students’ Perceptions of Learning Extensive Listening through YouTube Videos - Dzihnie, Zalfa Nabilah; Gozali, Agus (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to examine and describe vocational school students' perceptions of learning extensive listening through YouTube videos. The researcher used a mixed methods design to test students' perceptions of learning extensive listening through YouTube videos. Data were analysed quantitatively obtained from questionnaires and qualitatively obtained from the interview method. This study collected data from 36 students from SMKN 12 Malang. The results of the current study indicate students show positive perceptions of learning extensive listening through YouTube videos. A large number of students revealed that YouTube videos can enhance and motivate them to learn to listen extensively. The conclusions of the interviews were strengthened by the results, which that revealed students agreed among the application of YouTube videos for teaching extensive listening. In addition, students believe that YouTube videos are more useful when learning English, especially in teaching extensive listening.